Blood Flukes and Arterial Damage: A Review of Aneurysm Cases in Patients with Schistosomiasis - Valeria Silvestri; Vivian Mushi; Mwanahawa Idavas Mshana; Witness M. Bonaventura; Nyanda C. Justine; Deodatus Sabas; Billy Ngasala (Canadian Journal of Infectious Diseases and Medical Microbiology)
Introduction. Schistosomiasis, caused by trematode worms of the genus Schistosoma, has organ-specific morbidity due to host’s inflammatory response to the oviposition of parasite eggs in vessels and organs. Damage to the cardiovascular system, including aneurysms, has been described in patients. Aims and Methods. Aims of the review of case reports and series published in literature were to describe the occurrence of aneurysm in patients with schistosomiasis. Investigation Outcomes. A total of 13 cases (seven males and six females) with a mean age of 41.3 ± 14.9 years were included. Aneurysm occurred in patients with active or previous infection. In more than half of the cases, an intestinal or hepato-splenic involvement was reported, followed by pulmonary schistosomiasis and urinary or testicular involvement. The most frequently involved arterial district was the pulmonary artery. Immunomodulation and thrombophilia were featuring challenging surgery. Conclusions. More studies are needed to shed light on the vascular complications of schistosomiasis, to ascertain the true burden of aneurysms in patients with schistosomiasis, to establish the pathophysiology of vessel damage and aneurysm formation, and to assess if there is an association between schistosomiasis and aneurysm formation in line with WHO 2021–2030 NTD Roadmap.